COVID-19 and English council funding: What is the medium-term outlook? - Kate Ogden; David Phillips; Jean-Christophe Spiliotis (Institute for Fiscal Studies (IFS), 2020)
The COVID-19 crisis is having immediate effects on councils' budgets as a result of increases in spending on local services and reductions in income from sales, fees and charges (SFCs) and commercial activities. However, the crisis will cast a longer shadow on councils' finances. First, reductions in council tax and business rates revenues collected this year will feed through to budgets over the next three years. Second, some COVID-19-related spending pressures and reductions in revenues are likely to persist, and indeed could grow in a few cases. This report considers how councils' revenues and spending needs may evolve over the period to 2024-25, accounting for both the impact of COVID-19 and the pre-COVID funding outlook.
Keywords: 330; Coronavirus; Haushaltsplanung; Wirtschaftsprognose; England